2012
DOI: 10.3892/mmr.2012.884
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hypoxia-induced epithelial mesenchymal transition by luteolin in non-small cell lung cancer cells

Abstract: Abstract. Hypoxia-induced epithelial mesenchymal transition (EMT) is an essential step in cancer metastasis. Luteolin, a flavonoid that is widely distributed in plants, is a novel anticancer agent. However, the mechanism underlying its anticancer effects remains undefined. In this study, for the first time, we demonstrate that luteolin inhibits hypoxia-induced EMT in human non-small cell lung cancer cells in culture, which is demonstrated by the fact that hypoxia-induced EMT reduced the expression of E-cadheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…*p < 0.05 and **p < 0.01 indicate a significant difference from the control group compounds targeting EMT and angiogenesis have been the efficient therapeutic approach for the treatment of metastatic cancers . Luteolin, a flavonoid that is found in more than 300 plant species, has recently been shown to inhibit a variety of cancers, both in vitro and in vivo, with little to minimal toxicity (Lu et al, 2015;Ruan et al, 2012). Previous studies have shown that luteolin inhibits metastasis of triple-negative breast cancer cells through suppressing EMT (Cook et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05 and **p < 0.01 indicate a significant difference from the control group compounds targeting EMT and angiogenesis have been the efficient therapeutic approach for the treatment of metastatic cancers . Luteolin, a flavonoid that is found in more than 300 plant species, has recently been shown to inhibit a variety of cancers, both in vitro and in vivo, with little to minimal toxicity (Lu et al, 2015;Ruan et al, 2012). Previous studies have shown that luteolin inhibits metastasis of triple-negative breast cancer cells through suppressing EMT (Cook et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin treatment (5–50 μM) to non-small lung cancer cells could inhibit hypoxia-induced EMT as well as cell viability, proliferation and motility. The effect was at least partly through suppressing the expression of integrin β1 and FAK [87]. More importantly, luteolin administration (i.p.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Luteolin inhibits the expression of integrin β1 and focal adhesion kinase (FAK), which are closely related to EMT formation. This relationship suggests that luteolin inhibits hypoxia-induced EMT, at least in part, by inhibiting the expression of integrin β1 and FAK ( Ruan et al , 2012a ). Luteolin also inhibits EMT in malignant melanoma cells both in vitro and in vivo by regulating β3 integrin ( Ruan et al , 2012b ).…”
Section: Preventing Tumor Invasion and Metastasismentioning
confidence: 99%